2008
DOI: 10.1007/s10071-008-0188-6
|View full text |Cite
|
Sign up to set email alerts
|

The response of guide dogs and pet dogs (Canis Familiaris) to cues of human referential communication (pointing and gaze)

Abstract: The study raises the question of whether guide dogs and pet dogs are expected to differ in response to cues of referential communication given by their owners; especially since guide dogs grow up among sighted humans, and while living with their blind owners, they still have interactions with several sighted people. Guide dogs and pet dogs were required to respond to point, point and gaze, gaze and control cues of referential communication given by their owners. Results indicate that the two groups of dogs do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 42 publications
0
13
0
6
Order By: Relevance
“…Theall and Povinelli (1999) reported that chimpanzees did not discriminate between an attentive (eyes open) and inattentive (eyes close) human, whilst Hostetter et al (2001) showed that chimpanzees did discriminate between an attentive (facing toward) and inattentive (facing away) experimenter. In the case of dogs the head direction of humans seemed to be more important than the gaze, when comparing the performance of guide dogs of blind owners to pet dogs of sighted owners (Gaunet 2008;Ittyerah and Gaunet 2009). Furthermore, some studies showed wolves to be inferior (Hare et al 2002;Miklósi et al 2003;Virányi et al 2008) and others superior (Udell et al 2008) to dogs in their ability to read human cues and recognise their state of attention.…”
Section: Introductionmentioning
confidence: 98%
“…Theall and Povinelli (1999) reported that chimpanzees did not discriminate between an attentive (eyes open) and inattentive (eyes close) human, whilst Hostetter et al (2001) showed that chimpanzees did discriminate between an attentive (facing toward) and inattentive (facing away) experimenter. In the case of dogs the head direction of humans seemed to be more important than the gaze, when comparing the performance of guide dogs of blind owners to pet dogs of sighted owners (Gaunet 2008;Ittyerah and Gaunet 2009). Furthermore, some studies showed wolves to be inferior (Hare et al 2002;Miklósi et al 2003;Virányi et al 2008) and others superior (Udell et al 2008) to dogs in their ability to read human cues and recognise their state of attention.…”
Section: Introductionmentioning
confidence: 98%
“…Si los perros guía detectaran el estado atencional del dueño, utilizarían la comunicación visual en menor medida. Por otra parte compararon el de sempeño de ambos grupos en el seguimiento de diferentes claves humanas (dirección de la mirada y señalamiento) para encontrar comida oculta (Ittyerah & Gaunet, 2009). En este caso, la hipótesis en juego era que si la visión del dueño sirviera como clave en lacomponentes (acercamiento y robo).…”
Section: -Comparación De Perros Con Dueños Viden-tes Y No Videntesunclassified
“…De los nueve trabajos que utilizaron el movimiento de la cabeza junto con el de los ojos como estímulo para encontrar comida oculta, cinco indicaron que los perros se desempeñaron por encima del nivel del azar (Agnetta, Hare & Tomasello, 2000;Hare et al, 1998;Hare et al, 2002;Ittyerah & Gaunet, 2009;Soproni, Miklósi, Topál & Csányi, 2001). Dichos resultados fueron encontrados tanto con 18 como con 10 ensayos de entrenamiento.…”
Section: -Movimiento De La Cabeza Y Los Ojosunclassified
See 2 more Smart Citations